LEADER-4: blood pressure control in patients with type 2 diabetes and high cardiovascular risk. Issue 6 (June 2016) - Petrie, John R.; Marso, Steven P.; Bain, Stephen C.; Franek, Edward; Jacob, Stephan; Masmiquel, Luis; Leiter, Lawrence A.; Haluzik, Martin; Satman, Ilhan; Omar, Mohamed; Shestakova, Marina; Van Gaal, Luc; et al.
Abstract : Objective: As glucagon-like peptide-1 receptor agonists lower blood pressure (BP) in type 2 diabetes mellitus (T2DM), we examined BP control in relation to targets set by international bodies prior to randomization in the Liraglutide Effect and Action in Diabetes: Evaluation of cardiovascular outcome Results (LEADER) trial. Methods: We analyzed baseline data from LEADER (NCT01179048), an ongoing phase 3B, randomized, double-blind, placebo-controlled cardiovascular outcomes trial examining the cardiovascular safety of the glucagon-like peptide-1 receptor agonist liraglutide in 9340 people with T2DM from 32 countries [age (all mean ± SD) 64 ± 7.2 years, BMI 32.5 ± 6.3 kg/m 2, duration of diabetes 12.7 ± 8.0 years], all of whom were at high risk for cardiovascular disease (CVD). Results: A total of 81% ( n  = 7592) of participants had prior CVD and 90% ( n  = 8408) had a prior history of hypertension. Despite prescription of multiple antihypertensive agents at baseline, only 51% were treated to a target BP of less than 140/85 mmHg and only 26% to the recommended baseline BP target of less than 130/80 mmHg. In univariate analyses, those with prior CVD were prescribed more agents ( P  < 0.001) and had lower BP than those without (137 ± 18.8/78 ± 10.6 mmHg versus 140 ± 17.7/80 ± 9.9 mmHg; P  < 0.001). In logistic regression analyses, residency in North America (64% treated to <140/85 mmHg; 38% treated to <130/80 mmHg) was the strongest predictor of BP control. Conclusion: These contemporary data confirm that BP remains insufficiently controlled in a large proportion of individuals with T2DM at high cardiovascular risk, particularly outside North America. Longitudinal data from the LEADER trial may provide further insights into BP control in relation to cardiovascular outcomes in this condition. Abstract : Supplemental Digital Content is available in the text